Inclusion, reporting and analysis of demographic variables in chronobiology and sleep research - Tir, S; White, R; Spitschan, M (Frontiers Media, 2024)
Many aspects of sleep and circadian physiology are sensitive to participant-level characteristics. While recent research robustly highlights the importance of considering participant-level demographic information, the extent to which this information is consistently collected, and reported in the literature, remains unclear. This article investigates study sample characteristics within the published sleep and chronobiology research over the past 40 years. 6,777 articles were identified and a random sample of 20% was included. The reporting of sample size, age, sex, gender, ethnicity, level of education, socio-economic status, and profession of the study population was scored, and any reported aggregate summary statistics for these variables were recorded. We observed a significant upward trend in the reporting and analysis of demographic variables in sleep and chronobiology research. However, we found that while > 90% of studies reported age or sex, all other variables were reported in < 25% of cases. Reporting quality was highly variable, indicating an opportunity to standardize reporting guidelines for participant-level characteristics to facilitate Meta analyses.